Molecular characterisation of Flavobacterium spp. and investigation of their biofilm-forming capacity in the tilapia aquaculture system - Flemming, Leonard (Leonard Arnold) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2006.